SOCIO-HISTORICAL FOUNDATIONS OF THE FORMATION OF VOCAL ART - Otabekov Shokirjon Tursunali ugli (Academia Science Repository, 2023)
In this article, the history of vocal art, the socio-historical foundations of the formation of vocal art, the new directions of art studies and their analysis, the aesthetic-cultural studies direction of studying new problems of art are detailed. information provided.